Quantum Discord for d circle times 2 Systems - Ma, Zhihao; Chen, Zhihua; Fanchini, Felipe Fernandes [UNESP]; Fei, Shao-Ming (Nature Publishing Group, 2015)
We present an analytical solution for classical correlation, defined in terms of linear entropy, in an arbitrary d circle times 2 system when the second subsystem is measured. We show that the optimal measurements used in the maximization of the classical correlation in terms of linear entropy, when used to calculate the quantum discord in terms of von Neumann entropy, result in a tight upper bound for arbitrary d circle times 2 systems. This bound agrees with all known analytical results about quantum discord in terms of von Neumann entropy and, when comparing it with the numerical results for 10(6) two-qubit random density matrices, we obtain an average deviation of order 10(-4). Furthermore, our results give a way to calculate the quantum discord for arbitrary n-qubit GHZ and W states evolving under the action of the amplitude damping noisy channel.